2022
DOI: 10.1007/s00013-022-01715-3
|View full text |Cite
|
Sign up to set email alerts
|

A regularity result for a class of non-uniformly elliptic operators

Abstract: We obtain an explicit Hölder regularity result for viscosity solutions of a class of second order fully nonlinear equations led by operators that are neither convex/concave nor uniformly elliptic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For this equation with lower order terms, Ferrari and Vitolo [11] used methods from the viscosity theory to study ABP, Harnack and Hölder estimates, and later Ferrari and Galise [10] showed C 0,δ -regularity for δ = 1 − α 1 +α n ( √ α 1 + √ α n ) 2 ∈ (0, 1 2 ]. We note that δ = 1 2 holds if and only if α 1 = α n .…”
Section: Resultsmentioning
confidence: 99%
“…For this equation with lower order terms, Ferrari and Vitolo [11] used methods from the viscosity theory to study ABP, Harnack and Hölder estimates, and later Ferrari and Galise [10] showed C 0,δ -regularity for δ = 1 − α 1 +α n ( √ α 1 + √ α n ) 2 ∈ (0, 1 2 ]. We note that δ = 1 2 holds if and only if α 1 = α n .…”
Section: Resultsmentioning
confidence: 99%
“…About such approach, there are many contributions in literature. Among them, we wish to recall the following works [BGI18], [BGL17], [FV20b], [FG21], where the regularity of viscosity solutions of truncated operators has been studied. Moreover, always in the frame of a degenerate situation but in a non-commutative structures, we point out the results contained in [Fer20], [FV20a] and [Gof20].…”
mentioning
confidence: 99%